Fiscal policy in the crisis: Impact, sustainability, and long-term implications - Pier Carlo Padoan (Asian Development Bank Institute (ADBI), 2009)
The global economic and financial crisis has sparked an unprecedentedly large, generalized fiscal policy response in practically all major industrial and emerging economies, which will change the fiscal and macroeconomic landscapes for some time to come. This paper offers an overview of the new fiscal landscape looking at the following aspects: the size and composition of the fiscal stimulus packages of the major economies, the likely impact of such packages on aggregate demand and growth, the sustainability of countries' fiscal positions, and the international implications of the new fiscal landscape. It then considers under which conditions a virtuous scenario could develop that combines strong and balanced growth with fiscal sustainability. Finally, it offers some conclusions and lessons that can be shared by European and non-European economies.
Keywords: E62; F41; F42; 330; Finanzmarktkrise; Antizyklische Finanzpolitik; Wirkungsanalyse; Vergleich; Europa; Welt